2021
DOI: 10.1002/ehf2.13753
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intravenous ferric carboxymaltose on heart failure with preserved and reduced ejection fraction

Abstract: Aims Heart failure (HF) is a proinflammatory disease often associated with the onset of iron deficiency (ID). ID alters mitochondrial function, reducing the generation of cellular energy in skeletal muscle and cardiomyocytes. This study aimed to analyse the response of patients with HF to intravenous iron administration according to the type of HF: preserved ejection fraction (HFpEF) or reduced ejection fraction (HFrEF). Methods and results We conducted a retrospective, single‐centre study of 565 consecutive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 44 publications
(88 reference statements)
0
12
1
1
Order By: Relevance
“…No significant differences in adverse events were observed between the treatment groups 50 . A retrospective database analysis has shown that IV iron administration appears to improve ejection fraction and cardiac functional status in outpatients with iron deficiency, HFpEF, and HFrEF 52 …”
Section: Treatmentmentioning
confidence: 93%
See 1 more Smart Citation
“…No significant differences in adverse events were observed between the treatment groups 50 . A retrospective database analysis has shown that IV iron administration appears to improve ejection fraction and cardiac functional status in outpatients with iron deficiency, HFpEF, and HFrEF 52 …”
Section: Treatmentmentioning
confidence: 93%
“…50 A retrospective database analysis has shown that IV iron administration appears to improve ejection fraction and cardiac functional status in outpatients with iron deficiency, HFpEF, and HFrEF. 52 Another important aspect in the individualization of HF therapy is the use of vericiguat in patients with a recent episode of worsening HF requiring IV diuretic treatment. Using data from the VICTORIA trial, Senni et al found that plasma NT-proBNP may help to identify patients with worsening HFrEF, in whom the beneficial effects of vericiguat may be highest.…”
Section: Treatmentmentioning
confidence: 99%
“…127 In HF, iron deficiency can be due to an absolute decrease in total body iron or an inadequate distribution because of iron sequestration in the storage pool. 127 Although early studies provided the potential role of intravenous iron therapy in patients with HFrEF and HFpEF, 128,129 the role of iron supplementation in TAVI patients remains unconfirmed. One randomized trial is ongoing to explore the potential of intravenous iron therapy in TAVI patients (NCT 04797832) (Table 1).…”
Section: Iron Supplementationmentioning
confidence: 99%
“…In chronic HF, administration of ferric carboxymaltose (FCM) results in short-term (30 days) incorporation of iron into myocytes with an improvement of the left and right ventricular function [9,10]. In the medium term (3 months), a study by our group analysed the response of patients with HF to intravenous iron administration according to the type of HF, finding that intravenous iron administration improves ejection fraction and cardiac functional status in outpatients with ID and HF with both preserved and reduced ejection fractions [11]. Another study in the same line of research that was conducted on 890 patients who were consecutively admitted for acute heart failure (AHF) and received FCM administration before discharge showed a reduction in the combined event at 6 months (overall mortality, emergency department visits for decompensation, and readmissions) with a NNT close to 10 [12].…”
Section: Introductionmentioning
confidence: 99%